REKONSTRUKSI MODEL PEMBELAJARAN BAHASA ARAB DENGAN KERANGKA QUANTUM TEACHING - M. YUSUF SALAM (Ta'dib, 2012)
Quantum Teaching (QT) is a learning model developed by Bobby DePorter. QT emphasizes on the teacher skill in managing learning which facilitate the development of students’ potential. The major principle of QT is ‘bring their world our world and take our world into their world. To carry out the implementation of QT successfully, teachers need to consider context (environment) and content (instructional materials). In the context of Arabic learning which is constructed by means of QT, following framework: TANDUR which stands for Tumbuhkan (grow), Alami (be natural), Namai (name), Demontrasi (demonstrate), Ulangi (repeat) and Rayakan (celebrate).Kata kunci: quantum teaching, pembelajaran,  bahasa Arab